Shear resistance evaluation on the enamel surface of deciduous teeth following acid etching with or without previous air abrasion - Angela Cristina Cilense Zuanon; Ticiana Sidorenko de Oliveira Capote; Marina Machado Bordin (Brazilian Dental Science)
The purpose of this study was to evaluate the shear resistance of a composite resin to the enamel surface of deciduous teeth after acid etching surface with or without previous air abrasion. Sixteen sound exfoliated deciduous incisors were assigned to 2 groups. Group I was acid etched with 37% phosphoric acid and Group II was air abraded with 50-mm aluminum oxide particles for 15 seconds, at 80 psi and a 5-mm distance from the dental surface. The adhesive system Scotchbond Multi Purpose and Z100 composite resin was applied on both experimental groups. The Student’s t test demonstrated significant statistical difference between the groups (p=0.0001). The mean shear bond strengths for groups I and II are 10.65 MPa and 6.32 MPa, respectively. The authors concluded that the maximum bond strength was achieved by isolated acid etching, which yielded a significantly larger shear resistance than in combination with air abrasion.